Studies on Coordination Compounds of Some 3d-Transition Metal Ions with Acylthiosemicarbazide - Angelusiu, Madalina; Negoiu, Maria; L. Almajan, Gabriela; Rosu, Tudor; Saramet, Ioana (Asian Journal of Chemistry, 2010)
The synthesis of some coordination compounds of N1-[4-(4-bromophenylsulfonyl) benzoyl]-N4-(4-methylphenyl)thiosemicarbazide (BrATS) with CuCl2, Cu(CH3COO)2, Cu(SCN)2, Co(CH3COO)2, Ni(CH3COO)2, Cd(CH3COO)2 and ZnCl2 are described. The characterization of the complexes has been performed with the help of various physico-chemical techniques viz., IR, EPR, electronic spectroscopy, magnetic moments, thermogravimetric analysis, molar conductance and elemental analysis. Experimental data confirm the molar combination ratio M:L = 1:1 or 1:2 for the synthesized complexes. Room temperature ESR spectra of Cu(II) complexes yield (g) values characteristic of distorted octahedral and square-planar geometry.